Growth and characterization of crystalline Bi2Se3 thin films on flexible metal foils by magnetron sputtering system. (2022) - Singh, Bheem; Gautam, Sudhanshu; Aggarwal, V.; Tawale, J.S.; Kushvaha, S.S.
Abstract: We report the large area thin film deposition of Bi2 Se3 on flexible thin molybdenum (Mo) and titanium (Ti) metal foils using magnetron sputtering technique at temperature of 400 °C. The crystallinity of post-selenized thin film was investigated using x-ray diffraction and high intense peaks of Bi2 Se3 (0006) along other planes was obtained which showed the preferred orientation along c-axis on these polycrystalline substrates. Raman spectroscopy showed three main characteristic Raman peaks i.e. A 1 1g, E 2 g, and A 2 1g which revealed the formation of pure hexagonal phase of the Bi2 Se3 . Field emission scanning electron microscopy studied showed hexagonal nanoflakes shape Bi2 Se3 films with large granular sizes ranging from 200 to 450 nm and stoichiometry of Bi2 Se3 thin film was confirmed by energy dispersive x-ray analysis. The growth of crystalline hexagonal phase of Bi2 Se3 thin films on large area polycrystalline low cost flexible metal foils using magnetron sputtering system pave the way for futuristics flexible energy devices.